Mapping the Intellectual Structure: A Bibliometric Analysis of SME and Entrepreneurship Research in Nepal (2015-2024) - Shrestha, Hira Lal; Limbu, Suraj Kurungwang; Shrestha, Shraddha; Basnet, Asmita; Shrestha, Sneha (NPRC Journal of Multidisciplinary Research, 2025)
Background: Small and medium-sized enterprises (SMEs) play a vital role in the Nepalese economy, yet academic literature which has previously investigated them is vast and scattered. There is no comprehensive synthesis of this body of research that conceals over-arching themes, patterns of collaboration, and evolutionary changes.Objectives: The research maps the intellectual geography of Nepalese SMEs and entrepreneurship studies from the past decade (2015-2024). In particular, the research will determine hegemonic research topics, examine collaboration networks, examine publication trends, and determine leading contributing authors, institutions, and countries.Methods: Systematic searching was conducted in an academic database using a Boolean query ("Small" AND "Medium" AND "Entrepreneurs" AND "Nepal"). The search was restricted to open-access journal articles from 2015-2024 with a DOI, in Business, Economics, Finance, and Marketing disciplines, and a final dataset of 676 articles were retrieved. VOSviewer was used for bibliometric analysis to create network visualizations of thematic linkage and co-authorship. Descriptive analysis was performed to examine publication trends and contributor profiles.Findings: The review indicates high-level growth in publications, at its peak during the COVID-19 pandemic, projecting a research interest in crisis recovery and resilience. Thematic mapping identifies principal clusters on "economic growth," "policy," and "finance" and developing themes of "sustainability," "gender," and "innovation." Collaboration networks uncover high domestic contribution by Tribhuvan University as well as dense international contribution, particularly from the United States and United Kingdom but with collaboration clustering with key bridging authors. Business and Economics are predominant in the field but increasingly interdisciplinary.Conclusion: Nepalese SME studies are resilient and responsive to external shocks but thematically concentrated and disintegrated in collaboration. The topic would be enhanced by more integrated work that links evolving micro-themes like gender and sustainability with macroeconomic and policy core themes.Implication: The study provides a conceptual roadmap for researchers to identify gaps and initiate cross-disciplinary collaboration. To policymakers, the study pinpoints research areas well-studied and areas of potential still underexplored, pointing out where evidence-based intervention can be targeted most effectively towards benefitting the SME sector in Nepal.